The implementation of a behavioural support programme: Teachers' perceptions of the programme and themselves as providers. Issue 6 (3rd October 2016) - Ingemarson, Maria; Bodin, Maria; Rubenson, Birgitta; Guldbrandsson, Karin
Abstract : Purpose: The purpose of this paper is to investigate how teachers received and perceived the school programme Prevention in School (PS), a positive behavioural support programme; how did the teachers perceive the programme characteristics and themselves as providers; and how did this affect programme implementation? Design/methodology/approach: Qualitative methods with semi-structured interviews with 13 teachers and thematic content analysis were used. Findings: The teachers were heterogeneous in their views, with professional identity, programme understanding and experiencing change being important factors for the implementation. Ambiguities regarding the boundaries of the social assignment, opposition against the theoretical underpinnings and an unclear nomenclature in a core component affected the implementation negatively. Among the perceived benefits were instant rewards in the form of aha moments and increased self-awareness. The nature of the implementation barriers indicates that PS is in need of further development. Practical implications: Compatibility with teachers' ideologies, clarification of the social assignment and enough time to consider programme adoption are vital when implementing a programme like PS. Originality/value: The study provides context-specific understanding of teachers' perceptions of a behavioural support programme and of their role when trying to implement it. It is known that providers' perceptions affect the implementation and this study contributes to the field of implementation research, with particular respect to the school setting and comprehensive programmes like PS.